Green-Fluorescent Protein+ Astrocytes Attach to Beta-Amyloid Plaques in an Alzheimer Mouse Model and Are Sensitive for Clasmatodendrosis - Daschil, Nina; Humpel, Christian (Frontiers in Aging Neuroscience, 2016)
Alzheimer’s disease (AD) is pathologically characterized by beta-amyloid (Aβ) plaques and Tau pathology. It is well-established that Aβ plaques are surrounded by reactive astrocytes, highly expressing glial fibrillary acidic protein (GFAP). In order to study the cellular interaction of reactive astrocytes with Aβ plaques, we crossbred mice overexpressing amyloid precursor protein (APP) with the Swedish-Dutch-Iowa mutations (APP-SweDI) with mice expressing green fluorescent protein (GFP) under the GFAP-promotor. Three-dimensional confocal microscopy revealed a tight association and intense sprouting of astrocytic fine branched processes towards Aβ plaques in 12 month old mice. In order to study phagocytosis, 110 µm thick brain slices from 12 month old crossbred mice were cultured overnight, however, we found that the GFP fluorescence faded away, distal processes degenerated and a complete loss of astrocytic morphology was seen (clasmatodendrosis). In summary, our data show that GFP+ reactive astrocytes make intense contact with Aβ plaques but these cells are highly vulnerable for degeneration.